INDONESIA'S EFFORTS TO ADDRESS HUMAN RIGHTS VIOLATIONS AGAINST ITS SEAFARERS ON LONG XING VESSEL - Gymnastiar, Ibnu Alif Daffa; Burhanuddin, Agussalim (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM Azramedia indonesia, 2023)
This paper aims to discuss Indonesia's action in resolving the case of human rights violations of its seafarers on Chinese-flagged Long Xing vessels in 2020. In fact, there were 88 Indonesian seafarers who were distributed to fishing vessels named Long Xing owned by the Dalian Ocean Fisihing Co., Ltf group. However, it was revealed that there were violations of the seafarers' human rights on one of the vessels, Long Xing 629. These violations included drinking distilled seawater, working 18 hours per day, and salary deductions that ultimately affected the physical and mental health of the seafarers, leading to death and sea burial. This paper uses descriptive and analytical methods to explain what the Indonesian government did to resolve the viola tions of the Indonesian seafarers' human rights through diplomacy and law enforcement. As a result, the Indonesian Ministry of Foreign Affairs managed to hold a bilateral meeting with the Chinese Ministry of Foreign Affairs to confirm and conduct a thorough investigation. In addition, the Indonesian National Police named six suspects for distributing seafarers to Long Xing vessels in Indonesia for violating Law No. 21 of 2007. The Indonesian Ministry of Foreign Affairs represented by the Indonesian Embassy in Dakar successfully repatriated 88 Indonesian seafarers who worked at Long Xing vessels to return home safely after negotiations with the Senegalese government. The Indonesian government is committed to preventing similar cases against Indonesian seafarers from reoccurring.